Improved diagnostic accuracy when combining computed tomography angiography and corrected coronary opacification in patients with coronary stents. Issue 1 (2nd January 2017) - Dowsley, Taylor F.; Chepelev, Leonid; McArdle, Brian; Alam, Mohammed; Dwivedi, Girish; Chow, Benjamin J.W.
Abstract : Background The accuracy of coronary computed tomography angiography (CCTA) is sub-optimal in patients with coronary stents. Methods that can increase its diagnostic accuracy are desirable. Objective A proof-of-concept study was undertaken to determine if corrected coronary opacification (CCO) differences can improve the accuracy of CCTA in stented coronary arteries. Methods PCI patients who underwent both CCTA and invasive coronary angiography (ICA) within 3 months were analyzed. Coronary luminal attenuation values (normalized to the aorta) were measured proximally and distally to coronary stents. CCO differences were evaluated for ability to predict (i) stenosis on invasive angiography, (ii) abnormal resting coronary flow as measured by the corrected thrombolysis in myocardial infarction (TIMI) frame count (cTFC), and (iii) the combination of abnormal resting flow and significant stenosis on invasive angiography. Results Twenty-nine stented coronary arteries (n = 25, mean age =61.4 years, men =80.0%) were assessed. In stented coronary vessels, CCO identified stenosis (≥ 70%) with an area under the curve of 0.767 ( P = 0.021). CCO predicted abnormal resting coronary flow with high accuracy (AUC =0.867, P = 0.002). Combined CCTA/CCO identified both abnormal cTFC and stenosis ≥70% on ICA (functionally significant stenosis) with diagnostic accuracy of 92.3%. In contrast, CCTA visual assessment alone had lower diagnostic accuracy of 66.7% for identifying functionally significant stenosis. Conclusion CCO differences are predictive of abnormal resting flow and consequently, in-stent restenosis. Incorporation of this technique may improve the specificity of CCTA in PCI patients.